2002
DOI: 10.1007/s00213-002-1043-0
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation by antipsychotic agents of mitogen-activated protein kinase (MAPK) coupled to cloned, human (h)serotonin (5-HT)1A receptors

Abstract: Antipsychotics display contrasting efficacies in modulating MAPK phosphorylation at h5-HT(1A) receptors, ranging from high (e.g. S16924 and ziprasidone), via intermediate (e.g. clozapine) to low (e.g. haloperidol). Differential modulation of 5-HT(1A) receptor-coupled MAPK may contribute to their contrasting functional profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Clozapine and quetiapine are partial 5-HT 1A agonists in vitro (Newman-Tancredi et al 2001;Cussac et al 2002). Such actions do not appear to be involved in the drugs' cue properties in vivo.…”
Section: Tests With Dopaminergic Ligandsmentioning
confidence: 91%
“…Clozapine and quetiapine are partial 5-HT 1A agonists in vitro (Newman-Tancredi et al 2001;Cussac et al 2002). Such actions do not appear to be involved in the drugs' cue properties in vivo.…”
Section: Tests With Dopaminergic Ligandsmentioning
confidence: 91%
“…This pathway regulates cortical neurogenesis and synaptic proliferation and plasticity (Thomas and Huganir 2004), processes implicated in schizophrenia (Harrison and Weinberger 2005). Furthermore, the ERK cascade is differentially modulated by antipsychotic drugs in vitro (Cussac et al 2002;Lu and Dwyer 2005) and in vivo in a cell-specific manner (Fumagalli et al 2006). Specifically, in vivo clozapine reduced and haloperidol increased ERK activation in mouse dorsal striatum (Pozzi et al 2003), whereas in rat prefrontal cortex the converse was observed (Ahmed et al 2008).…”
Section: Introductionmentioning
confidence: 89%
“…Fourth, the atypical antipsychotic, clozapine, which displays improved capacity to treat negative symptoms with minimal liability for EPS, exhibits agonist properties at 5-HT 1A receptors in various in vitro models of receptor transduction (Assié et al 1997;Bruins Slot et al 2006;Cussac et al 2002;Elliott and Reynolds 1999;Newman-Tancredi et al 2005). The ability of clozapine to occupy 5-HT 1A receptors in nonhuman primates at clinically-relevant doses has been demonstrated by PET scans with [ 3 H]WAY100635 (Chou et al 2003).…”
Section: Introductionmentioning
confidence: 94%